State Housing Policy: The Experience of the Yamalo-Nenets Autonomous Okrug - USTINOVA, Oksana Vyacheslavovna; KHAIRULLINA, Nursafa Gafurovna; KOLTSOVA, Tatiana Alexsandrovna; SHVEDOVA, Marina Fedorovna; IVANYCHEVA, Tatyana Alekseevna (Journal of Advanced Research in Law and Economics, 2017)
Having the ability to improve one’s housing conditions is an important indicator of the growth of the well-being of the population, which is a prerequisite of the social and economic stability in the state. The market-oriented reforms in Russia resulted in the significant wealth disparity of the population. Given the high capital intensity of housing, for the majority of Russians it proves to be an overwhelming task to solve their housing problem and improve their living conditions on their own. Therefore, the solving of the housing problem of the citizens is one of the priorities of the state policy in the Russian Federation. The article deals with the specifics of the housing policy in Russia. It provides statistical and sociological data which characterize the issues of the state housing policy at the regional level (using the example of Yamalo-Nenets Autonomous Okrug). The measures contributing to the improvement of the efficiency of the housing policy are also proposed.